(untitled) (El-Wahat Journal for Research and Studies, 2023)
ملخص: سعت الدراسة إلى التعرف على واقع التدوير الوظيفي ودوره في الكفاءة الإنتاجية بالوزارات في قطاع غزة. حيث متطلبات التدوير الوظيفي (التدريب، تصميم الوظائف، استراتيجية التطور الوظيفي، النظم والإجراءات). هدفت الدراسة للتعرف على الكفاءة الإنتاجية للموظفين في المستويات الإدارية العليا. جمعت بيانات الدراسة باستخدام استبانة مؤلفة من (65) فقرة، وزعت على (380) موظفا من الفئة العليا عددهم (1863) موظفا، باستخدام طريقة العينة العشوائية. أمكن جمع (307) استبانة، بلغت نسبة الاستجابة (80.7%) من مجموع الاستبانات الموزعة. النتائج: احتلت استراتيجية التطور الوظيفي المرتبة الأولى، تلاها تصميم الوظائف، ثم التدريب وتطوير القدرات، وفي المرتبة الأخيرة النظم والإجراءات في الوزارات. وأظهرت الدراسة أن الكفاءة الإنتاجية جيدة بمتوسط حسابي نسبي بلغ (63.35%)، وأن هناك علاقة إيجابية بين متطلبات التدوير الوظيفي بأبعاده الأربعة وبين الكفاءة الإنتاجية. التوصيات: إشعار العاملين بأسباب ممارسة التدوير الوظيفي ومحاربة الرأي الذي يعتبر إن التدوير أسلوب عقاب، والاهتمام بمتطلبات التدوير الوظيفي لتأثيره على الكفاءة الإنتاجية للموظفين، والاهتمام بالتدريب للموظفين كأحد الاستراتيجيات المساعدة في تحسين وزيادة القدرات للموظفين. كلمات دالة: التدوير الوظيفي، الإنتاجية، التدريب، تصميم الوظيفة، التطور الوظيفي. Abstract: This research investigates the job rotation and its reflections on the Productivity at Ministries at Gaza Strip. Where the job rotation’s requirements according to the study are (training, job design, career development strategy, system and procedures). This study aims to identify the productivity efficacy for the first line and top-management employees. Data were collected by a questionnaire (65 paragraphs), which was distributed to (380) top-level employees. A number of (307) questionnaires were valid for analysis, the response percentage was (80.7%) out of the total distributed questionnaires. The following are the most important results: 1.Job development strategy has the highest effect on productivity efficacy, second job design, then training, and last job procedures. The study showed that top management productivity efficacy is good with a mean 63.35%. 2.There is a positive relationship between job rotation requirements and productivity efficacy. The most important recommendation: • Notify the employees that job rotation is used to improve performance not a punishment tool. • More concerned with job rotation requirements, the four fields, because of its effects on productivity. Key words: Job rotation, productivity, training, job design, career development.